Unconscious learning of likes and dislikes is persistent, resilient, and reconsolidates - Pine, Alex; Mendelsohn, Avi; Dudai, Yadin (Frontiers in Psychology, 2014)
Preferences profoundly influence decision-making and are often acquired through experience, yet it is unclear what role conscious awareness plays in the formation and persistence of long-term preferences and to what extent they can be altered by new experiences. We paired visually masked cues with monetary gains or losses during a decision-making task. Despite being unaware of the cues, subjects were influenced by their predictive values over successive trials of the task, and also revealed a strong preference for the appetitive over the aversive cues in supraliminal choices made days after learning. Moreover, the preferences were resistant to an intervening procedure designed to abolish them by a change in reinforcement contingencies, revealing a surprising resilience once formed. Despite their power however, the preferences were abolished when this procedure took place shortly after reactivating the memories, indicating that the underlying affective associations undergo reconsolidation. These findings highlight the importance of initial experiences in the formation of long-lasting preferences even in the absence of consciousness, while suggesting a way to overcome them in spite of their resiliency.